Metronomic therapy has low toxicity and is as effective as current standard treatment for recurrent high-risk neuroblastoma. (4th July 2017) - Berthold, Frank; Hömberg, Marc; Proleskovskaya, Inna; Mazanek, Pavel; Belogurova, Margarita; Ernst, Angela; Sterba, Jaroslav
ABSTRACT: The metronomic therapy concept uses low doses of continuously applied chemotherapeutic, anti-angiogenetic, and immunomodulating drugs. Twenty patients with recurrent and 3 with refractory high-risk neuroblastoma were treated by the metronomic concept using celecoxib, cyclophosphamide, vinblastine, and etoposide for up to 24 months. The outcome was compared to 274 matched patients with a first recurrence from stage 4 neuroblastoma using the variables time from diagnosis to first recurrence, number of organs involved, and MYCN amplification. All were treated with dose-intensive conventional chemotherapy. The study patients experienced 1–3 recurrences and had 1–3 sites involved (osteomedullary, primary tumor, central nervous system, lymph nodes, liver, lungs) before the metronomic therapy started. Two patients in complete remission and three with active refractory disease following recurrence treatment were excluded from the outcome analysis. The curves for secondary event-free and overall survival demonstrated no significant differences. The toxicity was minimal except for ≥3 grade thrombocytopenia and leukopenia (all heavily pretreated). The treatment was realized in an outpatient setting. The metronomic approach is similarly effective as standard treatment in recurrent high-risk neuroblastoma, has low toxicity, and is applicable in an outpatient setting. A prospective study including propranolol as a fifth drug is underway.